The Banishment of Accidents from Spinoza’s Paradise - Melamed, Yitzhak Y. Melamed (Acta Philosophica, 2022)
The paper traces the dramatic story of the fall of accidents from Spinoza’s paradise. In the first part of the paper, we will observe the accidents roaming freely – well, almost freely – in their pre-1663 paradise of Spinoza’s early works. The second part explains some highlights in the early history of accidents “before creation,” i.e., before their incarnation in Spinoza’s early ontological paradise. The third part will study the banishment, or systematic elimination, of accidents from Spinoza’s ontology after 1663. The fourth and final part will attempt to determine the sin which brought about the accidents’ punishment.